Conversion From Calcineurin to Mammalian Target of Rapamycin Inhibitors in Liver Transplantation: A Meta-Analysis of Randomized Controlled Trials. Issue 3 (March 2016) - Glover, Thomas E.; Watson, Christopher J.E.; Gibbs, Paul; Bradley, J. Andrew; Ntzani, Evangelia E.; Kosmoliaptsis, Vasilis
Abstract : Background: Conversion to mammalian target of rapamycin inhibitors (mTORi) is often used in liver transplantation to overcome calcineurin inhibitor (CNI) nephrotoxicity but the evidence base for this approach is not well defined. To summarize the evidence, from randomized clinical trials (RCTs), for conversion from CNI to mTORi-based immunosuppression after liver transplantation. Methods: Databases and conference abstracts were searched up to August 2015. The RCTs evaluating conversion from CNI to mTORi-based maintenance immunosuppression after adult liver transplantation. Descriptive and quantitative information was extracted; summary mean difference and risk ratio (RR) estimates were synthesized under a random-effects model. Heterogeneity was assessed using the Q statistic and I 2 . Results: Ten RCTs, with a total of 1927 patients, met the final inclusion criteria. Patients converted to mTORi had significantly better renal function at 1 year after randomization compared with patients remaining on CNI (mean difference, 7.48 mL/min per 1.73 m 2 ; 95% confidence interval [95% CI], 3.18-11.8). The risks of graft loss (RR, 0.77; 95% CI, 0.29-2.09; I 2, 31%) and patient death (RR, 1.05; 95% CI, 0.63-1.73; I 2, 0%) were similar for patients converted to mTORi and patients remaining on CNI. However, conversion to mTORi was associated with a higher risk of acute rejection (RR, 1.76; 95% CI, 1.33-2.34; I 2, 0%) and study discontinuation due to adverse events (RR, 2.17; 95% CI, 1.38-3.44; I 2, 63%) up to 1 year after randomization. Conclusions: Conversion from CNI to mTORi after liver transplantation is associated with improved renal function after 1 year but increases the risk of acute rejection and may be poorly tolerated. Abstract : This meta-analysis of patients converted from CNIs to mTORi in liver transplant patients is associated with an average 7.5 ml/min improvement in glomerular filtration rate, but 76% increase in acute rejection, and 117% increase in discontinuation due to adverse effects. Supplemental digital content is available in the text.